Theoretical Analysis of the Impact of CSO and CTB Distortions on BER Performances in Analog/M-QAM HFC/CATV Transmission Systems - Panagiev, O. B. (Elektronika ir Elektrotechnika, 2009)
A bit-error-rate (BER) performances analysis for a Hybrid fiber coaxial (HFC) network with subcarrier multiplexed AM-VSB/M-QAM transmission over an optical fiber is presented. It is shown that the BER of M-QAM channels in such systems can be significantly affected due to occasionally laser diode “clipping” of the analog signals. Here we analytically determine the amplitude distribution of composite distortions and the clipping noise by modeling it as a Weibull distribution. The results of the analysis are presented in a graphic mode. Ill. 6, bibl. 5, tabl. 1 (in English; abstracts in English, Russian and Lithuanian).